Covalent modification of primers improves PCR amplification specificity and yield - Schoenbrunner, Nancy J (Biol Methods Protoc, 2017)
We report a method for covalent modification of primers that enhances the specificity of PCR and increases the yield of specific amplification products at the end of PCR. The introduction of thermally stable covalent modifications, such as alkyl groups to the exocyclic amines of deoxyadenosine or cytosine residues at the 3′-ends of primers results in enhanced specificity of reactions. This higher specificity can result in greater sensitivity of detection by reducing competition with non-productive reactions. The reduction in the amplification of unintended byproducts is most apparent when both primers are modified at their respective 3′-ends. The T(M)s of such modified primers are only slightly affected by the inclusion of these modifiers. The principal mode of action is believed to be driven by the poor enzyme extension of substrates with closely juxtaposed bulky alkyl groups, such as would result from the replication of primer dimer artifact.